Design, Control and Implementation of Torus-Type Omniorientational Blimp With Tilting Actuators - Seung Hwan Song; Hyouk Ryeol Choi (IEEE Access, 2021)
Buoyancy-aided unmanned aerial vehicle (UAV) has a powerful advantage in terms of flight time and safety, compared to conventional multirotors. However, previously developed platforms showed limited flight maneuverability (i.e. omnidirectional translation) and posture transition (i.e. omniorientational rotation) owing to lack of number of actuators or limit of design specifications. As a solution, this study presents a symmetric torus blimp, which is pierced in the middle of envelope and surrounded by four tiltable actuator. All flight-aid electric parts are located in the center of the hole to match center of buoyancy with center of mass. And four motors mounted along the edge of the hull can be tilted by each linked servo. Owing to symmetric design and sufficient number and allocation of actuators, stable independent omniorientational and omnidirectional motion during flight that standard blimp or multirotors hard to do can be easily performed. This performance can be achieved by simple feedback control algorithm based on aerodynamic model. Also, a novel control allocation based on a fully-actuated system is described for independent orientation and position control. The result of various angle tracking orientation control and stabilization control experiments performed are presented. In addition, omnidirectional control with manual control keeping orientation independently is validated. Finally, narrow space passing and omnidirectional wall interaction results are described to demonstrate the advantages of the specification of this platform.